2022
DOI: 10.1177/09612033221122158
|View full text |Cite
|
Sign up to set email alerts
|

Serologic phenotypes distinguish systemic lupus erythematosus patients developing interstitial lung disease and/or myositis

Abstract: Objectives To determine if serologic phenotypes could be identified in systemic lupus erythematosus patients developing interstitial lung disease (ILD) and/or myositis. Methods Adult SLE patients (without myositis/ILD at baseline) had annual assessments and serum sampling between 2000 and 2017. New-onset ILD was identified using the SDI pulmonary fibrosis item. New-onset myositis was identified using the SLICC Damage Index muscle atrophy/weakness item, the SLEDAI-2K item for myositis, and annual creatinine kin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
1
0
Order By: Relevance
“…Two controversial points were raised during the analysis. First, we observed only a positive trend shown by creatinine in the bivariate analysis of AGEs levels in the whole sample [ 21 ]. We discussed if that trend could have a fictitious origin since patients with SLE had higher creatinine levels (although in normal range) and were mostly located in the third AGEs tertile, and also since the trend was not observed when we analyzed the two groups separately.…”
Section: Discussionmentioning
confidence: 99%
“…Two controversial points were raised during the analysis. First, we observed only a positive trend shown by creatinine in the bivariate analysis of AGEs levels in the whole sample [ 21 ]. We discussed if that trend could have a fictitious origin since patients with SLE had higher creatinine levels (although in normal range) and were mostly located in the third AGEs tertile, and also since the trend was not observed when we analyzed the two groups separately.…”
Section: Discussionmentioning
confidence: 99%
“…ILD can determine severe clinical symptoms, worsening survival rates in these patients [2]. The relationship between ILD and SLE is relatively rare [2][3][4][5][6]. However, individuals with overlapping connective tissue disease syndromes are highly prone to develop this manifestation [2].…”
Section: Systemic Lupus Erythematosusmentioning
confidence: 99%
“…The identification of specific phenotypes in the serum of SLE patients who develop ILD and/on myositis was the objective of a recent study. Cotton et al showed that KL-6, anti-Ro52, and anti-Ku were the most prevalent antibodies in patients with ILD/myositis [3].…”
Section: Ild In Slementioning
confidence: 99%